Characterization of soluble and insoluble fibers in artichoke by-products by ATR-FTIR spectroscopy coupled with chemometrics - Quintero Ruiz, Natalia Andrea (2021)
The objective of this study was to characterize the insoluble and soluble dietary fiber present in Argentine and Italian artichoke (Cynara scolymus) by-products by comparing chemical analysis and ATR-FTIR spectroscopy. Non-edible bracts of Argentine (AR) and Italian (Benevento (BN) and Sicily (SC)) artichoke cultivars were employed. The soluble and insoluble dietary fibers were extracted by physical procedures and determined by chemical, attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy, and chemometric analysis (principal components analysis, PCA). No differences in total dietary fiber content between AR and SC samples were observed, although they both showed higher values than BN. With respect to insoluble fiber, this fraction represents 82.5%, 63.5%, and 55.2% of the total dietary fiber for BN, SC and AR, respectively. Fibers from AR presented different compositions and structures, as determined by ATR-FTIR, compared to those of the Italian cultivars (BN and SC). Comparing the results of dietary fiber measured by ezymogravimetric assay with those obtained by ATR-FTIR and PCA, we conclude that it is possible to discriminate samples that contain different kinds of fiber using ATR-FTIR.